Clinic Management Information System (CMIS) / Wong Choong Leong - Wong, Choong Leong (2002)
Clinic Management Information System or in short (CMIS) is a system that computerize the clinics activities. In the current manual system, lots of problems exist in the management of a clinic. Hand written records are difficult to read. Besides, records are written in papers and placed in the cupboard. There are possibilities that the files misplaced or lost. The stocks of the drugs are difficult to be keeping track. CMIS however eliminate most of the problem facing by manual system. Records are stored securely in the database. Records are easily referred by the users of the system. CMIS is developed for three of users who comprise of doctors, staff and pharmacist. These users have their own restrictions in the system. Only the authorized users are allowed to create, maintain and make changes, delete or update the data under their respective scope. Validation of the user’s login is indeed needed in order to access to the system. With this system, the daily transactions are all computerized. Making the management running smooth, efficient, accurate and secured. The waterfall model with prototyping approach was chosen in the development phase because the strengths of both the model and prototyping can minimize the risk involved. The development tool chosen in this project is Visual Basic 6.0 with MS SQL Server as back-end database management system and Window 2000 as development platform. Finally, it is hopes that this project will bring a new era in the management of a clinic towards paperless environment.